A seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch and a preparation method thereof

By combining silicone rubber with natural plant fiber-reinforced PP materials and using crosslinker masterbatch to generate silicone rubber, the challenges of seamless airbag dashboard composites in low temperature toughness, gloss and soft touch are solved, achieving high performance, low gloss and soft touch effects.

CN116376169BActive Publication Date: 2025-03-11SHANGHAI PRET COMPOSITES +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211121476.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-15
Publication Date
2025-03-11
Estimated Expiration
2042-09-15

AI Technical Summary

Technical Problem

It is difficult to develop a seamless airbag instrument panel composite material with a good appearance, high performance, low gloss and soft touch, especially with excellent low temperature toughness and low gloss, providing a soft touch with great challenges.

Method used

Silicone rubber is combined with natural plant fiber reinforced PP material, and silicone rubber is generated at high temperature through crosslinker masterbatches, increasing the softness and soft touch of the instrument panel, while using natural plant fibers to improve the strength and rigidity of the material and reduce gloss.

Benefits of technology

It achieves a good appearance, high performance, low gloss and soft touch of the seamless airbag instrument panel, improves the low-temperature toughness and processing performance of the material, avoids appearance defects such as tiger skin, and improves production efficiency and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of polypropylene composite materials, and specifically discloses a composite material for an automobile dashboard with good appearance, high performance, low gloss and soft touch, and a preparation method thereof. The material comprises polypropylene, natural plant fiber, polysiloxane, crosslinking agent masterbatch, compatibilizer, color powder and other additives. The polypropylene composite material provided by the present invention improves the low-temperature brittleness of natural plant fiber reinforced polypropylene by adding polydimethylsiloxane, and at the same time gives the parts low gloss and soft touch, which can meet the high appearance requirements of the parts, save production costs, and is expected to replace leather covering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch, and a preparation method thereof. Background Art

[0002] As an extremely important functional and decorative part inside the car, the car dashboard needs to have certain strength, toughness, and good appearance requirements, and has always been the top priority of design and development of major OEMs. Among all plastic materials for dashboards, polypropylene materials used for hard plastic seamless airbag dashboards are the most demanding and difficult to develop products. Since such parts need to undergo high and low temperature airbag detonation tests, the material itself needs to have excellent low-temperature toughness without the protection of the foamed surface. In addition, the dashboard body, as the largest exposed area inside and outside the car, also needs a soft touch, beautiful texture, and a low gloss to bring a comfortable vision.

[0003] Therefore, it is necessary to develop a new type of low-gloss soft-touch material, which has excellent low-temperature toughness and the low gloss and soft touch unique to leather materials, and thus will have significant economic and social value.

[0004] CN111391451A discloses a method for manufacturing a flame-retardant composite material that is wear-resistant, stain-resistant and soft-touch, including preparing a substrate layer, and laying a soft elastic layer and a fluorine-containing compound film on the surface of the substrate layer in sequence. The patent obtains a stain-resistant soft-touch material by a multi-layer composite method, and the production efficiency is low in the actual production process, and the impact of this method on the performance of parts has not been mentioned. CN108929491A discloses a low-gloss, soft-touch automotive instrument panel composite material and a preparation method thereof, which is modified by blending copolymerized polypropylene and reinforcing agents and toughening agents. The patent mainly uses ethylene-octene copolymers and matting agents to improve the soft touch of PP materials and reduce the gloss of PP materials. However, the low-temperature performance of ethylene-octene is worse than that of silicone rubber, and its low-temperature resistance is limited, and it cannot bring consumers a natural appearance of imitating mica. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch, and a preparation method thereof. The silicone rubber used in the invention has the advantages of weather resistance and good low-temperature toughness. The addition of silicone rubber to natural plant fiber reinforced PP material can greatly improve the low-temperature impact of PP material. Since silicone rubber has a liquid structure before cross-linking, it can play a good lubricating effect in the extruder and injection molding process, which is beneficial to the processing of PP material, while avoiding appearance defects such as tiger skin patterns that are very easy to appear during the injection molding process of the instrument panel. The injection-molded instrument panel has the advantages of excellent appearance, good safety, high production efficiency, and low processing cost.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The seamless airbag instrument panel composite material of the present invention with good appearance, high performance, low gloss and soft touch is composed of the following raw materials in parts by weight:

[0008] Polypropylene: 27-96wt%

[0009] Natural plant fiber: 1-30wt%;

[0010] Polysiloxane 1-30wt%;

[0011] Crosslinking agent masterbatch: 0.1-5wt%;

[0012] Compatibilizer: 0.5~5wt%

[0013] Color powder 0.5-3wt%;

[0014] Other additives 0.1-1wt%.

[0015] in,

[0016] The polypropylene is a copolymer polypropylene with a melting index of 15 to 60 g / 10 min under the test conditions of 230° C. and 2.16 kg.

[0017] The natural plant fiber is pulp fiber, jute fiber, straw fiber, and the fiber diameter is 5-20 μm.

[0018] The polysiloxane is one or a combination of two of polydimethylsiloxane, polymethylvinylsiloxane and trifluoropropylmethylpolysiloxane.

[0019] The compatibilizer is one of polypropylene grafted vinyl triethoxy silane, polypropylene grafted mercaptopropyl triethoxy silane, polypropylene grafted aminoethyl-aminopropyl-trimethoxy silane and the like.

[0020] The toner is one or a combination of inorganic toners such as carbon black and titanium dioxide, and has a particle size of 0.05 to 1 μm.

[0021] The other auxiliary agents are a combination of three or more of hindered phenol antioxidants, phosphite antioxidants or hindered amine antioxidants.

[0022] The crosslinking agent masterbatch is composed of the following raw materials in percentage by weight:

[0023] Hydrogenated siloxane: 30-50 wt%;

[0024] Platinum catalyst: 2-10 wt%;

[0025] Polypropylene: 40-68wt%.

[0026] In the crosslinking agent masterbatch, the platinum catalyst is platinum chloride; the polypropylene is 230 ℃ , under the test conditions of 2.16kg, the melt index is between 3 and 9g / 10min, such as copolymer polypropylene, homopolymer polypropylene or random polypropylene, or one or more of the above compositions; the hydrogenated siloxane is one of hydrogenated methyl siloxane, hydrogenated ethyl siloxane, etc.

[0027] The preparation method of the crosslinking agent masterbatch comprises the following steps:

[0028] (1) Weigh the above parts by weight of polypropylene, siloxane, and platinum catalyst, add them into a high-speed mixer and stir at a low speed for 15 to 30 minutes;

[0029] (2) Add the mixture in the above mixer into an internal mixer and blend at 170-200° C. to obtain a crosslinking agent masterbatch.

[0030] The preparation method of the above-mentioned seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch comprises the following steps:

[0031] (1) First, polypropylene (PP), compatibilizer, color powder, other additives, etc. are weighed according to the above weight parts and mixed evenly, and glass fiber and polysiloxane are weighed according to the corresponding weight parts and mixed;

[0032] (2) The mixed PP raw materials are placed in the main feeding bin of the intermeshing co-rotating twin-screw extruder and fed into the barrel of the extruder through the feeding screw; the glass fiber mixture is fed into the extruder from the side feeding port. The extruder screw diameter is 35 mm, the aspect ratio L / D is 40, and the temperature of each zone of the main barrel from the feeding port to the die outlet is set to: 180°C, 180°C, 180°C, 190°C, 190°C, 200°C, 200°C, and the main barrel speed is 250 rpm. After melt extrusion, cooling, granulation, and drying, the process is completed.

[0033] (3) The above instrument panel composite material and the corresponding weight portion of cross-linking agent masterbatch are added into a high-speed mixer and mixed evenly, and then added into an injection molding machine for injection molding, the injection molding temperature is 190-230° C., and the mold temperature is 50-100° C. After the injection molding is completed, a seamless airbag instrument panel with good appearance, high performance, low gloss and soft touch can be obtained.

[0034] The beneficial effects of the present invention are:

[0035] (1) The crosslinking agent masterbatch used in the invention is easy to migrate to the surface during injection molding due to the high mold temperature. The crosslinking agent masterbatch and polysiloxane can undergo a crosslinking reaction at high temperature to generate silicone rubber, which increases the softness of the instrument panel surface and improves the soft touch of the instrument panel surface. Silicone rubber has excellent weather resistance and low-temperature toughness, which solves the low-temperature explosion failure problem of seamless airbag instrument panels, broadens and improves the application of PP materials in the field of seamless airbag instrument panel components, and greatly improves the safety of seamless airbag instrument panels. At the same time, polysiloxane is a liquid and has good wettability on natural fibers. Compared with conventional elastomers such as ethylene octene copolymers during the processing of PP materials, the processing performance is better, avoiding the risk of tiger-skin appearance defects that are easy to appear in conventional elastomers in PP, and improving the surface appearance of the instrument panel.

[0036] (2) Natural plant fibers are added to PP materials to improve the strength and rigidity of the materials. At the same time, natural plant fibers and silicone rubber have low gloss, which can further reduce the gloss of PP materials in PP materials. Combined with the softness of silicone rubber, it is expected to replace the use of leather such as PVC, improve the grade of dashboard parts, improve production efficiency, and reduce costs. The special appearance of natural plant fibers themselves, when used with color powder, makes the surface of the dashboard have the appearance of imitating natural mica, further improving the surface appearance of the dashboard. DETAILED DESCRIPTION

[0037] The present invention can be further described by the following preferred embodiments, but these embodiments are only for illustration and do not limit the scope of the present invention.

[0038] In the composite material formula of the embodiment and the comparative example, the polypropylene resin is provided by SK Chemicals, and the trade name is BX3900. The natural plant fiber is cellulose fiber, provided by Lenzing Group, and has a diameter of 5 μm. The polysiloxane is polydimethylsiloxane, provided by Dow Corning, and has a trade name of PMX-200. The polypropylene resin in the crosslinker masterbatch is copolymer polypropylene provided by Li Changrong Chemical, and has a trade name of 7533; the platinum catalyst is platinum chloride, provided by Hubei Xinghengye Technology Co., Ltd.; the hydrogenated siloxane is polymethyl hydrogen siloxane provided by Dow Corning, and has a trade name of MHX-1107. The compatibilizer is polypropylene grafted with vinyl triethoxysilane, which is homemade. The specific method is that the compatibilizer mainly extrude the molten polypropylene and vinyl triethoxysilane under the action of peroxide. The color powder is carbon black, provided by Cabot Corporation, and has a particle size of 15nm. The antioxidants are provided by BASF and British ICE, with the trade names of Irganox 1010, Irganox 168 and Negonox DSTP.

[0039] Examples A1-A3 and Comparative Examples B1-B2 are preparations of crosslinked masterbatches

[0040] According to the ratio in Table 1, the siloxane hydride, platinum catalyst and polypropylene were mixed and added to a high-speed mixer and stirred at a low speed for 15 to 30 minutes; the mixture in the mixer was added to an internal mixer and blended at 180° C. to obtain a crosslinking agent masterbatch.

[0041] Table 1 Distribution ratio of each group of Examples A1-A2 and Comparative Examples B1-B2 (parts by weight)

[0042] Components Example A1 Example A3 Example A3 Comparative Example B1 Comparative Example B2 Hydrosiloxane 35 40 45 45 Platinum catalyst 3 5 8 8 Polypropylene 62 55 47 55 92

[0043] According to the ratios in Table 2 and Table 3, polypropylene and the crosslinker masterbatch shown in Table 1 are melt-mixed in a twin-screw extruder with a length-to-diameter ratio of 40:1, extruded and granulated, and the extrusion temperature is between 180-200°C. The modified material and the corresponding weight portion of the crosslinker masterbatch are added to a high-speed mixer and mixed evenly, and then added to an injection molding machine for injection molding, the injection molding temperature is 190-210°C, and the mold temperature is 80°C. After the injection molding is completed, a seamless airbag instrument panel with good appearance, high performance, low gloss and soft touch can be obtained. The instrument panel material after injection molding is sampled on the part, and the relevant test results are shown in Table 4.

[0044] Mechanical properties: The tensile strength of the material is tested according to the IS0 527 test method, the test condition is 50mm / min; the bending modulus of the material is tested according to the ISO178 test method, the test condition is 2mm / min, and the span is 64mm; the notched impact strength of the material is tested according to the ISO 179 test method, and the test condition is -30℃; the glossiness is tested according to the ISO 2039 test method; the hardness is tested according to the ISO2039 Shore D method. The surface appearance of the parts is mainly obtained by naked eye observation.

[0045] Table 2 Distribution ratio of each group of Examples 1-7 (parts by weight)

[0046]

[0047]

[0048] Table 3 Comparative Examples 1-4 Distribution Ratios (Parts by Weight)

[0049]

[0050] Table 4 Mechanical properties and gloss test results of Examples 1-8 and Comparative Examples 1-4.

[0051]

[0052] It can be seen from Examples 1-3 that under the same crosslinker masterbatch, by increasing the content of polysiloxane in the natural plant fiber system, the low-temperature notched impact strength of the system is significantly increased, the surface hardness is also significantly reduced, and the surface gloss is also reduced. Under the premise of crosslinker masterbatch, increasing the content of polysiloxane, the low-temperature impact performance, hardness and gloss of the parts are significantly optimized. From the results of Examples 3, 4 and Comparative Example 3, it can be seen that when the content of natural fiber is increased, the rigidity of the parts is improved, while the low-temperature notched impact strength is reduced, the hardness is improved, and the gloss is reduced. The effect of natural fiber on parts is to improve rigidity and reduce gloss. From the results of Examples 4, 5, 7 and Comparative Examples 1 and 2, it can be seen that the formula design of the crosslinking aid masterbatch has a greater impact on the low-temperature notched impact strength and surface hardness of the parts. Crosslinking aid masterbatch A2 helps to promote the crosslinking amplitude of polysiloxane, improve the low-temperature toughness of parts, and reduce the surface hardness of parts. The optimal ratio of hydrogenated siloxane and platinum catalyst in crosslinker masterbatch A2 is controlled at a level of 8:1, which has a better effect on parts. It can be seen from the results of Examples 5 and 6 that when the content of polysiloxane in the system is high, increasing the content of crosslinking agent masterbatch A2 can significantly improve the low-temperature toughness of the parts, reduce the surface hardness significantly, and have no significant effect on rigidity. It can be seen from the results of Examples 6 and 8 that the compatibilizer is also effective for the dispersion of silicone rubber and natural fibers in PP. As the content of the compatibilizer increases, the rigidity of the parts is further reduced, and the low-temperature toughness, surface hardness and glossiness are further reduced. Therefore, in order to achieve the excellent effect of the appearance of the parts, the use of compatibilizers is inevitable, and appropriate compatibilizers are beneficial to the overall safety and appearance of the parts. At present, in the 20% natural plant fiber reinforced PP material system, 20wt% polysiloxane is added, and the addition amount of 5wt% compatibilizer is optimal, and the appearance, gloss, performance and touch of the parts are the best. It can be seen from the results of Examples 6, 8 and Comparative Example 4 that compared with the traditional ethylene octene copolymer elastomer, the low-temperature toughening effect of the cross-linked polysiloxane is more obvious, the rigidity is slightly improved, and a better rigid-toughness balance is achieved. The parts of the traditional ethylene octene copolymer elastomer system have serious tiger-skin appearance defects, while the parts of other polysiloxane toughening systems have good appearance. At the same time, the hardness and gloss of the surface of the parts prepared by the cross-linked polysiloxane are lower, which fully improves the soft touch effect of the parts and improves the grade of the parts. In the future, it is expected to replace the effect of leather coating, improve production efficiency and reduce costs. It can be seen from the seamless airbag instrument panel after injection molding in Example 8 that the surface of the instrument panel is close to the appearance effect of leather coating, and the appearance defects such as tiger-skin pattern on the surface of the parts are not observed. This appearance is recognized by the automobile factory.

[0053] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.

Claims

1. A seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch, characterized in that: It is composed of the following raw materials in parts by weight: Polypropylene: 27-96wt% Natural plant fiber: 1-30wt%; Polysiloxane 1-30 wt%; Crosslinker masterbatch: 0.1-5 wt%; Compatibilizer: 0.5~5wt% Color powder 0.5-3wt%; Other additives 0.1-1wt%; The crosslinking agent masterbatch comprises the following raw materials in weight percentage: Hydrogenated siloxane: 30~50wt%; Platinum catalyst: 2~10wt%; Polypropylene: 40~68wt%; The hydrogenated siloxane is one or a combination of hydrogenated methyl siloxane, methyl phenyl hydrogenated siloxane and hydrogenated ethyl siloxane; The polysiloxane is one or a combination of two of polydimethylsiloxane, polymethylvinylsiloxane and trifluoropropylmethylpolysiloxane.

2. The seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch according to claim 1, characterized in that: The platinum catalyst is platinum chloride; the polypropylene is one or a combination of two or more of copolymer polypropylene, homopolypropylene or random polypropylene with a melt index between 2 and 10 g / 10 min under the test conditions of 230° C. and 2.16 kg.

3. The seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch according to claim 1, characterized in that: The preparation method of the crosslinking agent masterbatch is as follows: (1) Weigh the above weight parts of polypropylene, hydrosiloxane, and platinum catalyst, add them into a high-speed mixer and stir at a low speed for 15 to 30 minutes; (2) Add the mixture in the above mixer into an internal mixer and blend at 170-200° C. to obtain a crosslinking agent masterbatch.

4. The seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch according to claim 1, characterized in that: The polypropylene is a copolymer polypropylene with a melting index between 10 and 100 g / 10 min under the test conditions of 230° C. and 2.16 kg.

5. The seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch according to claim 1, characterized in that: The natural plant fiber is one of cellulose fiber, ramie fiber, straw fiber and jute fiber, and has a diameter of 5-30 μm.

6. The seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch according to claim 1, characterized in that: The compatibilizer is one or a combination of two of polypropylene grafted vinyl triethoxysilane, polypropylene grafted mercaptopropyl triethoxysilane, and polypropylene grafted aminoethyl-aminopropyl-trimethoxysilane.

7. The seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch and the preparation method thereof according to claim 1, characterized in that: The toner is one or a combination of carbon black and titanium dioxide inorganic toner, and the particle size is 0.05-10 μm.

8. The seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch and the preparation method thereof according to claim 1, characterized in that: The other auxiliary agents are one or more of hindered phenol antioxidants, phosphite antioxidants or hindered amine antioxidants.

9. The seamless airbag instrument panel composite material with good appearance, high performance, low gloss and soft touch and the preparation method thereof according to claim 1, wherein the steps are as follows: (1) First, polypropylene (PP), compatibilizer, color powder, and other additives are weighed according to the above weight parts and mixed evenly, and then the corresponding weight parts of natural plant fiber and polysiloxane are weighed and mixed; (2) The mixed PP raw material is placed in the main feeding bin of an intermeshing co-rotating twin-screw extruder, and is fed into the barrel of the extruder through the feeding screw; the natural plant fiber mixture is fed into the extruder from the side feeding port; the extruder screw diameter is 35 mm, the aspect ratio L / D is 40, the temperature of each zone of the main barrel from the feeding port to the die outlet is set to: 180°C, 180°C, 180°C, 190°C, 190°C, 200°C, 200°C, the main barrel speed is 250 rpm, and after melt extrusion, cooling, granulation, and drying treatment, a seamless airbag instrument panel composite material with good appearance, high performance, low gloss, and soft touch is obtained; (3) The above-mentioned instrument panel composite material and the corresponding weight portion of cross-linking agent masterbatch are added into a high-speed mixer and mixed evenly, and then added into an injection molding machine for injection molding. The injection molding temperature is 190-230°C and the mold temperature is 50-100°C. After the injection molding is completed, a seamless airbag instrument panel with good appearance, high performance, low gloss and soft touch can be obtained.

Citation Information

Patent Citations

  • Low-gloss and soft-tactility automobile dashboard composite material and preparation method thereof

    CN108929491A

  • Manufacturing method of wear and stain resistant flame-retardant composite material with soft touch

    CN111391451A

  • Polypropylene composite material as well as preparation method and application thereof

    CN109721929A